PARAMETERS OF THE SYNCHRONOUS GENERATOR AND THE FACTORS INFLUENCING THEM - J. N. Abdullaev (Journal Park Publishing, 2024)
Synchronous generators are one of the important electromechanical devices, and their normal operation can be influenced by certain factors. This article will analyze the operating modes of synchronous generator in Almalyk thermal power plant, important parameters and factors affecting them.
Keywords: thermal power plant, turbo generator, power factor, cooling air, overload, normal operation, apparent power.